Solving Shortage Control Problem in Inventory Production Using Genetic Algorithm (مجلة المنصور, 2022)
This paper has been focused on an improvement on the application of traditional methods using genetic algorithm. Genetic algorithm considers one of the random searching algorithms that based on the mechanism of natural selection and natural genetics. This improvement has implemented on inventory production model that has a deficit. Experimental result has been illustrated that applying genetic algorithm on petrol production was better than applying traditional methods because of that the total costdown when using genetic algorithm in order to cover the shortage in production.